Exposure to the predator odor TMT induces early and late differential gene expression related to stress and excitatory synaptic function throughout the brain in male rats. (25th August 2020) - Tyler, Ryan E.; Weinberg, Benjamin Z. S.; Lovelock, Dennis F.; Ornelas, Laura C.; Besheer, Joyce
Abstract: Persistent changes in brain stress and glutamatergic function are associated with post‐traumatic stress disorder (PTSD). Rodent exposure to the predator odor trimethylthiazoline (TMT) is an innate stressor that produces lasting behavioral consequences relevant to PTSD. As such, the goal of the present study was to assess early (6 hours and 2 days—Experiment 1) and late (4 weeks—Experiment 2) changes to gene expression (RT‐PCR) related to stress and excitatory function following TMT exposure in male, Long‐Evans rats. During TMT exposure, rats engaged in stress reactive behaviors, including digging and immobility. Further, the TMT group displayed enhanced exploration and mobility in the TMT‐paired context 1 week after exposure, suggesting a lasting contextual reactivity. Gene expression analyses revealed upregulated FKBP5 6 hours post‐TMT in the hypothalamus and dorsal hippocampus. Two days after TMT, GRM3 was downregulated in the prelimbic cortex and dorsal hippocampus, but upregulated in the nucleus accumbens. This may reflect an early stress response ( FKBP5 ) that resulted in later glutamatergic adaptation ( GRM3 ). Finally, another experiment 4 weeks after TMT exposure showed several differentially expressed genes known to mediate excitatory tripartite synaptic function in the prelimbic cortex ( GRM5, DLG4 and SLC1A3 upregulated), infralimbic cortex ( GRM2 downregulated, Homer1 upregulated), nucleus accumbens ( GRM7 and SLC1A3 downregulated), dorsal hippocampus ( FKBP5 and NR3C2 upregulated, SHANK3 downregulated) and ventral hippocampus ( CNR1, GRM7, GRM5, SHANK3 and Homer1 downregulated). These data show that TMT exposure induces stress and excitatory molecular adaptations, which could help us understand the persistent glutamatergic dysfunction observed in PTSD. Abstract : Predator odor (TMT) stress induces early and latent gene expression adaptations of molecular targets associated with PTSD.